A personalized mandibular implant with supporting and porous structures designed with topology optimization – a case study of canine. Issue 2 (4th March 2019) - Cheng, Kangjie; Liu, Yunfeng; Yao, Chunyan; Zhao, Wenquan; Xu, Xu
Abstract : Purpose: The purpose of this study is to obtain a titanium mandibular implant that possesses a personalized external shape for appearance recovery, a supporting structure for physiological loading and numerous micro-pores for accelerating osseointegration. Design/methodology/approach: A three-dimensional intact mandibular model of a beagle dog was created from cone-beam computerized tomography scans. A segment of the lower jaw bone was resected and replaced by a personalized implant with comprehensive structures including a customized external shape, supporting structures and micro-pores, which were designed by topology optimization. Then with FEM analysis, the stress, displacement distribution and compliance of the designed implant were compared with the non-optimized model. The weight of the optimized implant that was fabricated by SLM with titanium alloy powder was measured and contrasted with the predicted non-optimized model for evaluating the viability of the design. Findings: The FEM results showed the peaks of von Mises stress and displacement on the optimized implant were much lower than those of the implant without optimization. With topology optimization, the compliance of the implant decreased significantly by 53.3 per cent, and a weight reduction of 37.2 per cent could be noticed. Originality/value: A design strategy for personalized implant, with comprehensive structures and SLM as the fabrication method, has been developed and validated by taking a canine mandible as the case study. With comprehensive structures, the implant presented good biomechanical behaviors thanks to the most appropriate supporting structures obtained by optimal design. The topological optimal design combined with SLM printing proved to be an effective method for the design and fabrication of personalized implant with complex structures.